Medical residency training: contributions for qualification and provision of physicians in Brazil - Berger, Carla Baumvol (2017)
Objective: This paper discusses medical residency training. The experience of implementing a national medical residency program is introduced and considerations about the issues that came across during this process are commented. Methods: Concepts about training internalization, decentralization and deconcentration, debating the meaning of these terms from the experience reported. Results: Some of the challenges perceived indicate the need to reorganize similar processes to overcome the low occupancy of places in medical residency and to enable skills for the follow up of preceptors-to-be. Conclusion: This innovation is a contribution for qualification and provision of physicians for the Brazilian Unified Health System.